Studi Literatur Pengaruh Kuat Arus, Waktu Perendaman, Dan Suhu Terhadap Hasil Elektroplating - Suyanto, Suyanto; Wibowo, Riyanto (Universitas Ivet, 2024)
Currently, electroplating is widely used in the metal industry for various purposes, including improving the appearance and also preventing corrosion. Besides that, the mechanical properties of materials such as strength and hardness are also affected so that they will increase. The electroplating process is a process for coating metal by dipping the material to be coated into an electrolyte solution that carries a direct electric current to the dipped electrode. The materials coated in the electroplating process are usually low and medium carbon steel. The coating materials that are often used are nickel, chrome, zinc and copper. Electroplating process variables greatly influence the results achieved. In this article, we will discuss the influence of current strength, immersion time, and temperature of the electrolyte solution on the results of the electroplating process. The properties of electroplating results discussed are layer thickness, corrosion resistance, and hardness.